(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2025)
The fluctuating price of crystal guava has a direct impact on the efficiency level of crystal guava marketing. The Mirit Sub-district, as the production center of crystal guava in Kebumen Regency, needs to examine the efficiency of the marketing channels. This research aims to determine (1) the number of marketing channels, (2) the value of marketing margin, (3) the value of farmer’s share, (4) the level of marketing efficiency, and (5) the impact of price sensitivity on Mirit Sub-district’s crystal guava in Kebumen Regency. The research location is determined by using the purposive sampling method. 50 crystal guava farmers are determined by using the proportional random sampling method, while 12 crystal guava traders are determined by using the snowball sampling method. The results of the research indicate the following that (1) there are three marketing channels for crystal guava namely Marketing Channel I involves Farmers - Local End Consumers, Marketing Channel II involves Farmers - Collectors - Retailers - Local End Consumers, Marketing Channel III involves Farmers - Collectors - Wholesalers - Retailers - Local End Consumers; (2) Channel III is the longest channel with the largest marketing margin, which is Rp 6.667/kg, and Channel I is the shortest channel which has the smallest marketing margin; (3) Channel III has the smallest farmer’s share value, which is 45,21%, and Channel I has the largest farmer’s share value, which is 100%.; (4) Channel I has the most efficient channel; (5) The marketing channel has less efficient as the selling price decreases.